IMPLEMENTATION OF CONTEXTUAL LEARNING IN DEVELOPING THE RELIGIOUS CHARACTER OF DANCE, DRAMA, AND MUSIC EDUCATION STUDENTS - Ayu Janianti Yusuf (Teladan: Jurnal Pendidikan Umum dan Karakter, 2026)
Islamic Religious Education plays a strategic role in developing students' religious character in higher education. However, rapid technological and social changes require innovative learning approaches that connect religious teachings with students' real-life experiences. This study aims to describe the implementation of contextual learning in Islamic Religious Education courses and its contribution to the development of religious character among students of the Dance, Drama, and Music Education Study Program at Universitas Negeri Makassar. This research employed a descriptive qualitative approach. Data were collected through observation, in-depth interviews, and documentation, and analyzed using the Miles and Huberman model, including data reduction, data display, and conclusion drawing. The findings indicate that contextual learning was implemented through connecting learning materials with students' experiences, case discussions, self-reflection, project-based activities, and collaborative learning. These strategies enhanced students' understanding of Islamic values and encouraged the internalization of religious character, including discipline in worship, responsibility, honesty, tolerance, and social awareness. Contextual learning provides meaningful learning experiences that enable students to relate religious concepts to their daily lives. The study concludes that contextual learning is an effective approach to supporting the development of students' religious character in higher education.